Feathered diplomacy: when birds become main factors of research design and geography on Vigur Island - David Pierre Milesi-Gaches (Rivista Italiana di Ornitologia - Research in Ornithology, 2024)
Vigur Island, situated in Iceland’s Westfjords, is renowned for its diverse avian species, such as Atlantic Puffins and Black Guillemots, and its marine inhabitants including Harbour and Grey Seals. Despite its openness to tourism, the island is a subject of ongoing conservation efforts. This opinion paper argues for a more holistic approach to research on the island, highlighting the complex interplay between human activity and the island’s ecosystem. It critiques the current, often narrow, research methodologies that fail to fully account for the intricate relationships between species and their environment. The paper calls for a re-evaluation of habitat classification to incorporate the significant impact of avian populations and stresses the importance of adhering to Icelandic laws that mandate minimal disturbance to wildlife. With seasonal closures and careful management practices like eiderdown collection, Vigur Island serves as a model for balancing human interests with ecological integrity. This opinion advocates for adaptable, comprehensive research strategies that, while illustrated through the case of Vigur, should be applied universally, urging scientists to embrace broader perspectives in environmental studies globally.